The Green Tetrahymena utriculariae n. sp. (Ciliophora, Oligohymenophorea) with Its Endosymbiotic Algae (Micractinium sp.), Living in Traps of a Carnivorous Aquatic Plant - Pitsch, Gianna; Adamec, Lubomír; Dirren, Sebastian; Nitsche, Frank; Šimek, Karel; Sirová, Dagmara; Posch, Thomas (Journal of eukaryotic microbiology, 2017)
The genus Tetrahymena (Ciliophora, Oligohymenophorea) probably represents the best studied ciliate genus. At present, more than forty species have been described. All are colorless, i.e. they do not harbor symbiotic algae, and as aerobes they need at least microaerobic habitats. Here, we present the morphological and molecular description of the first green representative, Tetrahymena utriculariae n. sp., living in symbiosis with endosymbiotic algae identified as Micractinium sp. (Chlorophyta). The full life cycle of the ciliate species is documented, including trophonts and theronts, conjugating cells, resting cysts and dividers. This species has been discovered in an exotic habitat, namely in traps of the carnivorous aquatic plant Utricularia reflexa (originating from Okavango Delta, Botswana). Green ciliates live as commensals of the plant in this anoxic habitat. Ciliates are bacterivorous, however, symbiosis with algae is needed to satisfy cell metabolism but also to gain oxygen from symbionts. When ciliates are cultivated outside their natural habitat under aerobic conditions and fed with saturating bacterial food, they gradually become aposymbiotic. Based on phylogenetic analyses of 18S rRNA and mitochondrial cox1 genes T. utriculariae forms a sister group to Tetrahymena thermophila.
Keywords: symbióza; protozoální DNA; Plants; Mitochondria; sekvence nukleotidů; Oxygen; Ecosystem; fylogeneze; RNA, Ribosomal, 18S; cévnaté rostliny; Chlorophyta; stadia vývoje; Phylogeny; Ecology; DNA, Protozoan; rostliny; Animals; Ciliophora; kyslík; ekologie; zvířata; Tetrahymena; Life Cycle Stages; Oligohymenophorea; ekosystém; Tetrahymena thermophila; Base Sequence; Symbiosis; RNA ribozomální 18S; mitochondrie; Tracheophyta